Effect of Molecular Coupling on Ultrafast Electron‐Transfer and Charge‐Recombination Dynamics in a Wide‐Gap ZnS Nanoaggregate Sensitized by Triphenyl Methane Dyes. Issue 5 (16th November 2015) - Debnath, Tushar; Maity, Partha; Dana, Jayanta; Ghosh, Hirendra N.
Abstract: Wide‐band‐gap ZnS nanocrystals (NCs) were synthesized, and after sensitizing the NCs with series of triphenyl methane (TPM) dyes, ultrafast charge‐transfer dynamics was demonstrated. HRTEM images of ZnS NCs show the formation of aggregate crystals with a flower‐like structure. Exciton absorption and lumimescence, due to quantum confinement of the ZnS NCs, appear at approximately 310 and 340 nm, respectively. Interestingly, all the TPM dyes (pyrogallol red, bromopyrogallol red, and aurin tricarboxylic acid) form charge‐transfer complexes with the ZnS NCs, with the appearance of a red‐shifted band. Electron injection from the photoexcited TPM dyes into the conduction band of the ZnS NCs is shown to be a thermodynamically viable process, as confirmed by steady‐state and time‐resolved emission studies. To unravel charge‐transfer (both electron injection and charge recombination) dynamics and the effect of molecular coupling, femtosecond transient absorption studies were carried out in TPM‐sensitized ZnS NCs. The electron‐injection dynamics is pulse‐width‐limited in all the ZnS/TPM dye systems, however, the back electron transfer differs, depending on the molecular coupling of the sensitizers (TPM dyes). The detailed mechanisms for the above‐mentioned processes are discussed. Abstract : A sensitive situation : Wide‐band‐gap ZnS NCs form strong charge‐transfer (CT) complexes with the triphenyl methane series of dyes (pyrogallol red, bromopyrogallol red, and aurin tricarboxylic acid) with the appearance of new CT absorption bands. PGR and Br‐PGR form stronger CT complexes with ZnS NCs than ATC, due to the presence of the catecholate moiety rather than a salicylate moiety. This leads to a faster charge recombination (fast back electron transfer) reaction for the PGR/ZnS and Br‐PGR/ZnS systems.